Chondrosarcoma of the Pelvis: Oncologic and Functional Outcome. (2000) - Wirbel, Reiner J.; Schulte, Michael; Maier, Bernd; Koschnik, Martin; Mutschler, Wolf E.
Abstract : Purpose. Chondrosarcoma (CS) most commonly involves the pelvis. The factors that influence local and systemic control of pelvic CS and the functional outcome should be evaluated. Patients. Fifty-one patients (37 males and 14 females; mean age, 39.4 years) with pelvic CS were included in this retrospective study. Methods. The tumor stage, surgical treatment, surgical margin achieved, complications, incidence of local recurrence (LR), incidence of distant metastases, and the oncologic and functional status were evaluated. Oncologic outcome was estimated by the method of Kaplan and Meier, and the functional status was scored according to Musculoskeleral Tumor Society (MSTS) criteria. Analysis of variance was used to determine the factors that influence the oncologic and functional outcome. Results. Surgical stages were IA in three cases, IB in 23, IIB in 23, and III in two. Hemipelvectomy (H) was performed in 13 cases, internal hemipelvectomy (IH) with endoprosthetic replacement in 17, and continuity resection (CR) in 23.Two patients received IH and CR, one due to LR, and one due to instability. Radical or wide margins were achieved in 27 cases, marginal margins in 16, and intralesional margins in eight. Local complication required additional surgery in 10 cases due to local infections and/or hematomas.Two patients died perioperatively. In 48 out of the 49 remaining patients, follow-up was available with a mean duration of 73.4 months (range, 4–229 months).Twenty patients died of the disease, two patients are alive with metastases, four patients are disease free after LR, and 22 patients show no evidence of the disease. LR occurred in 10 cases (20.4%), and 17 patients (34.6%) developed distant metastases. Functional evaluation of the 28 survivors revealed good and excellent results in 19 cases, fair in three and poor in six.The mean MSTS score of all survivors was 69.2%, after H it was 37.6%, after IH was 61.4%, and after CR was 79.5%. Conclusion. In pelvic chondrosarcoma, survival was determined by the tumor stage and the surgical margin achieved.The incidence of LR was influenced by the surgical margin achieved, whereas the incidence of distant metastases was influenced by the tumor stage. The best oncologic results in chondrosarcoma involving the innominate bone could be found in low-grade tumors, and the best functional results after continuity resection and restoration of the pelvic girdle.